Opinii, atitudini şi comportamente politice în cadrul stilurilor de viaţă - Urse, Laureana (Calitatea Vieții, 1992)
The paper outlines the political attitudes, opinions and behaviours of workers and intelectuals from four cities of our country ( București, Cluj, Iași and Tîrgu-Mureș) as a result of the field research unfolded in October 1991 regarding the way of life and life styles in Romania.